Adherence to antidepressants - Abimbola Farinde (Archives of Global Professionals, 2013)
While major depression is considered a frequent mental illness there are ongoing reports of high non-adherence to antidepressant medications which places suffers at high risk for relapse, recurrence, or greater impairment,. The World Health Organization (WHO) defines adherence as the extent to which a person's behavior (e.g. taking medications) can align with the agreed recommendations of a health care provider. Unfortunately while patient may recognize the importance of adherence to antidepressant medications the majority of patients do not adhere to their prescribed antidepressants. Some of the factors that may contribute to or lead to non-adherence include knowingly or unknowingly missing doses, taking extra doses, delaying administration times, or taking drug holidays. Pharmacists have the unique ability to deter non-adherence through the performance of continuous assessment and monitoring of adherence in this population given these accessibility. Additionally, pharmacists are able to develop therapeutic alliances with patients that can help to increase the likelihood of achieving positive patient outcomes. Antidepressant non-adherence can be viewed as a significant public health concern so it is important for patients to be educated about the importance of adherence, and health care professionals should be aware of factors or patient characteristics that can serve as barriers to non-adherence.